If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -41 = 17 Reorder the terms: -41 + 2x = 17 Solving -41 + 2x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '41' to each side of the equation. -41 + 41 + 2x = 17 + 41 Combine like terms: -41 + 41 = 0 0 + 2x = 17 + 41 2x = 17 + 41 Combine like terms: 17 + 41 = 58 2x = 58 Divide each side by '2'. x = 29 Simplifying x = 29
| 9x-74=11x | | 525=900-300p | | (-3-1x)(1-2x)(x+3)= | | y=7x^2+21x-2 | | 8.25w=-74.25 | | -8+Y=-29 | | Z+13=-5 | | 9.25m=-74 | | A+13=-15 | | z+13=-15 | | w-15=19 | | 3x-1=a | | 100=(12x+8)-(4x+4) | | 50=(12x+8)-(4x+4) | | 87-6x=12x+19 | | 8-7x=108-42x | | 2q+348=876 | | -13-9=7x+19 | | (25*0.4)+(x*0.6)=100 | | 135-4x=4x+23 | | 1+2+3+4+5+6+7+8+9+0=45 | | 1+2+3+4+5+6+7+8+9+0=100 | | 1+2+3+4+5+6+7+8+9+0= | | 56+6=62 | | x^2*x= | | 12-6x=-7x | | 1567+8534=10101 | | 1567+8534= | | -7x-12x-3x^2= | | 3x-21=46 | | -3x*-1x= | | 18+z=14 |